2017
DOI: 10.1111/jth.13604
|View full text |Cite
|
Sign up to set email alerts
|

C‐type lectin‐like receptor 2 promotes hematogenous tumor metastasis and prothrombotic state in tumor‐bearing mice

Abstract: Background C-type lectin-like receptor 2 (CLEC-2) is a platelet activation receptor of sialoglycoprotein podoplanin, which is expressed on the surface of certain types of tumor cells. CLEC-2-podoplanin interactions facilitate hematogenous tumor metastasis. However, direct evidence of the role of CLEC-2 in hematogenous metastasis and cancer progression is lacking. Objective and methods We generated immunological CLEC-2-depleted mice by using anti-mouse CLEC-2 monoclonal antibody 2A2B10 and investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 41 publications
1
116
0
3
Order By: Relevance
“…demonstrated that CLEC‐2‐deficiency in mice was protective against thrombosis and hematogenous metastasis. Thrombus formation in tumor vessels was significantly inhibited in CLEC‐2‐depleted mice bearing podoplanin‐expressing B16F10 melanoma cells . Payne et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that CLEC‐2‐deficiency in mice was protective against thrombosis and hematogenous metastasis. Thrombus formation in tumor vessels was significantly inhibited in CLEC‐2‐depleted mice bearing podoplanin‐expressing B16F10 melanoma cells . Payne et al .…”
Section: Resultsmentioning
confidence: 99%
“…Podoplanin is a sialomucin‐like glycoprotein and has the ability to induce platelet aggregation via interacting with the C‐type lectin‐like receptor (CLEC)‐2 on platelets . Recent experimental studies using mouse models confirmed the important role of podoplanin in the pathophysiology of VTE . Based on these observations, podoplanin‐induced platelet aggregation might be a major driver of brain tumor‐associated VTE.…”
Section: Introductionmentioning
confidence: 99%
“…MMP2, FcgRIIa, and ADP are involved in the direct activation of platelets by tumor cells . The mechanism of platelet CLEC‐2 activation by tumor podoplanin was recently analyzed, and CLEC‐2 deficiency was found to inhibit tumor metastasis . Similarly, in osteosarcoma, mouse platelets are activated by osteosarcoma cells, and PDGF from activated platelets promotes tumor growth .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some pathways are distinctive of a particular cancer. For example, the expression of circulating microparticle-associated tissue factor increases the thrombotic risk predominantly in pancreatic cancer 3,4 ; or the expression of podoplanin, a ligand for C-type lectin receptor type 2 on platelets, in glioblastoma multiforme, 5 or the cell surface expression of long-chain polyphosphates on tumour-derived prosteasomes in prostate cancer, which activate coagulation in a factor XII-dependent manner. 6 Tumours may also indirectly promote thrombosis through the induction of thrombocytosis or leucocytosis, both of which are part of some published thrombotic risk score.…”
mentioning
confidence: 99%